DETERMINANT FACTORS IN THE FORMATION OF STUDENTS’ ISLAMIC PERSONALITY AT INDONESIAN SCHOOL OF BANGKOK (SIB) 2018 - Andriyani, Andriyani (Ar Raniry : International Journal of Islamic Studies, 2018)
Education is a necessity for every human being. In Islam, education is evidenced by changes in attitudes and behavior in accordance with Islamic doctrine that requires activities and environment to support its success, so it can be said that Islamic education is the formation of a Muslim personality. This study was conducted at Indonesian School of Bangkok (SIB) located in Thailand with cross sectional design. The results of statistical analysis showed that students who got Islamic Education in the family environment well tend to 7,636 times have a good Islamic personality, while students who got Islamic Education in school well, tend to be 6,238 times have a good Islamic personality. Islamic education in the family environment had most significant relationship with the formation of students’ Islamic personality in SIB Thailand.